Supplemental methionine selenium effects on egg yolk physicochemical, functional, and protein structure during storage - Chen, Dan; Liu, Yaotong; Xu, Shiwen (Frontiers in Nutrition, 2023)
To clarify the effect of the addition of methionine selenium on the physicochemical, functional, and protein structural properties of egg yolk during storage. We analyzed the changes in the main indicators of egg yolks stored at 4°C and 25°C for 28 days. The results showed that the increase in water content and pH, and the decrease in absolute zeta potential and apparent viscosity of the selenium-rich egg yolks (Se-group) during storage were smaller than those of the control group egg yolks (C-group). In addition, the antioxidant capacity and emulsifying ability of the Se-group during storage were better than those of the C-group. Simultaneously, the hardness and chewiness of the Se-group gel during storage were lower than those of the C-group. The protein structure results showed that selenium rich treatment did not affect the secondary structure of egg yolk protein during storage but could improve the fluorescence intensity of the egg yolk protein. Therefore, the addition of methionine selenium can reduce the degree of deterioration in the physicochemical properties of egg yolk during storage and extend its shelf life.